A survey about knowledge of exhaled nitric oxide use among Southern Italian pulmonologists and trainees - Marinelli, Alessio; Dragonieri, Silvano; Portacci, Andrea; Maselli, Leonardo; Lulaj, Ernesto; Carpagnano, Giovanna Elisiana (Acta Biomedica Atenei Parmensis, 2024)
Background and aim of the study. We aimed to perform a survey to evaluate the knowledge of exhaled nitric oxide (FeNO) use among a group of pulmonologists and trainees within several respiratory departments in southern Italy. Methods. All participants were asked to fulfill an online survey including 19 true or false questions about several aspects of FeNO use. The questionnaire was kept anonymous, and data were not accessible to anyone except the operators. Results. A total number of 94 surveys were collected (51 specialists, 43 trainees). The median score was 14 for both pulmonologists and trainees (IQ 25-75: 13-16 and 12-15, respectively, p=ns). No significant differences in terms of age of experience (5 years) were detected in the group of specialists. Among trainees, those attending the first year had lower scores compared to the second, third and fourth year (p=0.05, 0.01 and 0.05, respectively). Conclusions. Our data showed an adequate knowledge about the use of FeNO concerning the diagnosis and management of asthma. Nonetheless, the understanding of FeNO use and interpretation in relation to other respiratory conditions and co-morbidities must be improved in both specialists and trainees. Finally, as expected, first year trainees had overall less knowledge regarding FeNO.